Water stewardship and North America's food and beverage companies: a case study in corporate sustainability. (2016) - Jones, Peter; Comfort, Daphne; Hillier, David
The aim of this paper is to provide an exploratory review of the extent to which the leading North American food and beverage companies are publicly addressing water stewardship. The findings reveal that the vast majority of the selected companies address a number of elements concerning water stewardship as part of their more general approach to CSR. However, corporate commitments to water stewardship can be interpreted as being driven as much by business imperatives as by any specific concerns for CSR or a fundamental desire to maintain the viability and integrity of natural ecosystems. More critically the authors suggest that the selected companies' commitments to water stewardship are framed within existing business models focused on technological improvements in eco-efficiency and continuing economic growth.